SKALA USAHA DAN DIVERSIFIKASI PRODUK TAHU DI KABUPATEN OKU TIMUR - Serly Novita Sari (Jurnal Bakti Agribisnis, 2015)
The purpose of this study is to: (1) To know the scale of the business of tofu industry in East OKU Regency, (2) To know the diversification of tofu products produced by tofu industry in East OKU Regency, (3) Calculate the amount of expenses incurred, acceptance and Profit gained from the know-making business in East OKU Regency. This research will be conducted in OKU Timur Regency. Determining the location is done purposively with consideration that in OKU Timur Regency is not soybean production center, but there are many business units of tofu manufacture consisting of tofu chinese, tofu half cooked and fried tofu. The study was conducted in July 2014. The study found that the R / C ratio of tofu industry ratio with soybean requirement> 1,000 Kg per month was 1.23. The R / C ratio of tofu industry ratio with soybean requirement of 500-1000 Kg per month is 1.15. The R / C ratio of tofu industry ratio with soybean requirement <500 Kg per month is 1.17. Based on the calculation of R / C ratio, the industry ratio of more than 1 (R / C> 1) indicates that the know-making business in OKU Timur Regency is profitable. Know-how with soybean requirement> 1,000 Kg per month has the greatest R / C ratio of 1.23 This shows the business of making tofu with soybean requirement> 1000 Kg per month is more profitable than other tofu industry.